Effectiveness of Miklowitz family-focused therapy using cyberspace on the quality of relationships in patients with bipolar disorder - Abdi, Elham; Rahimian Boogar, Isaac; Elmi Manesh, Nila; Ghorbani, Raheb (Researcher Bulletin of Medical Sciences, 2024)
Objective: This study aimed to determine the effectiveness of family-focused therapy using cyberspace on the quality of relationships in patients with bipolar disorder. Materials and Methods: The present study is a quasi-experimental with pretest-posttest design with a follow-up period. The statistical population includes patients with bipolar disorder who were referred to counselling centers and psychological services with one of their family members, from which 30 patients were selected by purposive sampling with a family member. Then Miklowitz intervention was performed using cyberspace for the experimental group and the control group was not trained. The tools of this research included the Pierce (1991) Quality of Relationships Questionnaire. Results: The analysis results with repeated measures showed that Miklowitz intervention using cyberspace was significant in the quality scores of the experimental group and control scores, and this difference was greater in the experimental group (P <0.05). Conclusion: As a result, it can be said that family-focused therapy with the Miklowitz approach improves the quality of family relationships and improves the level of family health in patients with bipolar disorder.